Nebraska - Frederick, Michael (Author) ([Michael Frederick], 2020)
"A Midwest family drama series about a talented group of strangers who come together to help Freddy Bland make his first documentary that can raise his awareness. There will be resistance." --
Keywords: Documentary films -- Fiction; Nebraska -- Fiction; Middle West -- Fiction